2021
DOI: 10.3389/fnsys.2021.768762
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Prediction and Surprise: A Role for Active Sleep at the Dawn of Consciousness?

Abstract: The brain is a prediction machine. Yet the world is never entirely predictable, for any animal. Unexpected events are surprising, and this typically evokes prediction error signatures in mammalian brains. In humans such mismatched expectations are often associated with an emotional response as well, and emotional dysregulation can lead to cognitive disorders such as depression or schizophrenia. Emotional responses are understood to be important for memory consolidation, suggesting that positive or negative ‘va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 219 publications
(275 reference statements)
0
26
0
1
Order By: Relevance
“…While it is not evident how to study emotions in insects (but see [87]), it could be argued that arousal systems more generally are employed to detect prediction errors and thereby promote learning [88]. Thus, we and others have suggested that active sleep might be crucial for optimizing prediction, and attention, and learning [2,67,89], and this may involve different kinds of homeostatic mechanisms centered on brain circuits rather than cells. Our finding that dFB-induced active sleep in Drosophila upregulates different nAchRa subunits is consistent with new findings that these subunits regulate appetitive memories in flies [90] and that cholinergic systems more generally underpin learning and memory in this animal [91].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…While it is not evident how to study emotions in insects (but see [87]), it could be argued that arousal systems more generally are employed to detect prediction errors and thereby promote learning [88]. Thus, we and others have suggested that active sleep might be crucial for optimizing prediction, and attention, and learning [2,67,89], and this may involve different kinds of homeostatic mechanisms centered on brain circuits rather than cells. Our finding that dFB-induced active sleep in Drosophila upregulates different nAchRa subunits is consistent with new findings that these subunits regulate appetitive memories in flies [90] and that cholinergic systems more generally underpin learning and memory in this animal [91].…”
Section: Discussionmentioning
confidence: 97%
“…Henceforth, we call this 'quiet' sleep, in contrast to the 'active' sleep that seems to be engaged by dFB activation [2,10]. Notably, calcium imaging of spontaneous sleep bouts in Drosophila also revealed active and quiet sleep stages [10], suggesting that both of our experimental approaches are physiologically relevant.…”
Section: Thip-induced Sleep Decreases Brain Activity and Connectivitymentioning
confidence: 94%
See 2 more Smart Citations
“…Несмотря на некоторое сходство переживаемых в сновидении событий с реальностью у спящего снижается волевая активность и произвольный контроль над собой и происходящими событиями (Nir & Tononi, 2010). Отсутствие самоконтроля во время сна может быть связано со снижением активности таких областей мозга, как нижняя теменная, орбитофронтальная, дорсолатеральная и префронтальная кора (Van De Poll & van Swinderen, 2021;Vertes & Linley, 2021). Действительно, было показано, что снижение активности в префронтальной области коры во время сенсорного восприятия в бодрствовании сопровождалось снижением самосознания (Yang & Lewis, 2021;Kim et al, 2022).…”
Section: психические механизмы в быстром снеunclassified